Further In Vitro and Ex Vivo Pharmacological and Kinetic Characterizations of CCF219B: A Positive Allosteric Modulator of the α1A-Adrenergic Receptor - Robert S. Papay; Dianne M. Perez (Pharmaceuticals)
Background: Alterations in the adrenergic system have been associated with the pathophysiology of Alzheimer’s disease (AD). A novel α1A-adrenergic receptor (AR)-positive allosteric modulator (PAM), CCF219B, has been shown to outperform donepezil with rescue of AD cognition/memory deficits with a reduction in amyloid biomarkers and without cardiovascular side effects. Initial pharmacological analysis in transfected cell lines revealed a signal bias with increased efficacy (but not potency) of cAMP signaling and ligand selectivity for norepinephrine (NE). As most GPCR allosteric modulators change the potency of agonists, we hypothesized and now report that CCF219B induced additional aspects of its allosteric interactions with NE that may provide mechanistic insight. Methods: Using Rat-1 fibroblasts stably transfected with α1A-AR, we determined the activation profile of pERK and p38 messengers by CCF219B in the presence of NE. Using membranes prepared from the stably transfected fibroblasts or from the brain of WT mice or the AD mouse model, hAPP(lon), equilibrium or kinetic radioligand-binding analyses were performed. Results: We identified p-ERK1/2 but not p38 as an additional signal pathway that is potentiated by CCF219B in the presence of NE. An analysis of binding studies of CCF219B in membranes derived from the brains of WT or hAPP(lon) mice revealed profiles that were time-dependent and resulted in an increase in α1A-AR expression that was unaltered in the presence of cycloheximide or when performed at 37 °C. hAPP(lon) mice displayed a reduction in α1A-AR-binding sites that were rescued upon prolonged incubation with CCF219B but also displayed a compensatory increase in α1B/D-AR subtype expression. Binding kinetics reveal that CCF219B can decrease the association rate of 3H-NE but only in the presence of GTP. The association rate increased for the radiolabeled antagonist, 125I-HEAT. There were no changes in the dissociation rate of either radiolabel. Conclusions: CCF219B affects the association but not the dissociation rate of NE and explains its ability to increase the active state of the receptor by promoting a pre-coupled conformation, consistent with increasing efficacy but not potency. Potentiation of pERK may contribute to CCF219B’s ability to confer neuroprotection and be pro-cognitive in AD. CCF219B’s ability to increase the expression of α1A-AR provides a positive feedback loop and strengthens the hypothesis that α1-AR subtypes may be involved in AD etiology and/or progression.